The reformation for armchair theologians - Sunshine, Glenn S., 1958- (Louisville, Westminster John Knox Press, 2005)
This readable, accessible narrative story of the Protestant Reformation is written for lay audiences. It is part of the popular Westminster John Knox Press Armchair series and is illustrated with memorable cartoons by Ron Hill. The chapters of the book are suitable for use in church adult education settings to provide a solid grounding in the history of the Reformation and its leading ideas. Questions for discussion and suggestions for further reading provided for each chapter make this book great for group study. Since the Protestant Reformation is such a formative event in the lives of churches, it is important to have an accessible resource to tell its story available for laypersons in all denominations. Written by experts but designed for the nonexpert, the Armchair series provides accurate, concise, and witty overviews of some of the most profound moments and theologians in Christian history. These books are an essential supplement for first-time encounters with primary texts, a lucid refresher for scholars and clergy, and an enjoyable read for the theologically curious.
On the eve of the Reformation -- Martin Luther and the break with Rome -- Reform of Word and Sacrament -- Divisions -- The Sacramentarian controversy and the spread of Zwinglianism -- Catholic reform or counter-reform? -- The empire strikes back -- John Calvin : biography -- "The most perfect school of Christ" -- Spain and the Dutch revolt -- The Reformation in England and Scotland -- The Reformation in France -- The Thirty Years' War and the end of the era.
Includes bibliographical references (pages 235-236) and index.
Keywords: Reformation